New technologies create opportunities - Sally Murray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper argues that new technologies - for communication, such as mobile phones and the internet, but also for manufacturing, agriculture, energy, and transport - have the potential to bridge many of the productivity gaps between sub-Saharan Africa and more advanced developing and developed countries. Technology can help to overcome distances between producers and consumers, knowledge and skills gaps, and energy shortfalls, and can bring down the costs of living to make wages competitive. However, new technologies will not deliver these gains unaided: supportive policies are required to create an environment where these new technologies can deliver on their potential.
Keywords: O14; O25; O33; O55; 330; Africa; industrialization; technology